Who gets vaccinated? Cognitive and non-cognitive predictors of individual behavior in pandemics - Mark Andreas Andor; Thomas K. Bauer; Jana Eßer; Christoph M. Schmidt; Lukas Tomberg (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This study investigates the different cognitive and non-cognitive characteristics associated with individuals' willingness to get vaccinated against Covid-19 and their actual vaccination status. Our empirical analysis is based on data obtained from three survey waves of about 2,000 individuals living in the German state of North Rhine-Westphalia. We find that individuals with a high level of trait reactance display a significantly lower willingness to get vaccinated. They also tend to get inoculated later or never. Moreover, neuroticism, locus of control, and risk literacy appear to be associated with the willingness to get vaccinated, but these results are less pronounced and less robust. Our results indicate that vaccination campaigns and policies could be improved by specifically addressing those with a high level of trait reactance. – – Diese Studie untersucht die verschiedenen kognitiven und nicht-kognitiven Merkmale, die mit der Bereitschaft von Personen, sich gegen Covid-19 impfen zu lassen, und ihrem tatsächlichen Impfstatus zusammenhängen. Unsere empirische Analyse basiert auf Daten aus drei Erhebungswellen mit rund 2.000 Personen in Nordrhein-Westfalen. Es zeigt sich, dass Personen mit einer hohen Merkmalsreaktanz eine signifikant geringere Bereitschaft zur Impfung zeigen. Sie neigen auch dazu, sich später oder nie impfen zu lassen. Darüber hinaus scheinen Neurotizismus, Kontrollüberzeugung und Risikokompetenz mit der Impfbereitschaft in Zusammenhang zu stehen, allerdings sind diese Ergebnisse weniger ausgeprägt und weniger robust. Unsere Ergebnisse deuten darauf hin, dass Impfkampagnen und -maßnahmen verbessert werden könnten, indem man sich speziell an Personen mit einem hohen Maß an Merkmalsreaktivität wendet.
Keywords: D91; H0; I12; I18; 330; Covid-19; vaccination; psychological traits; risk literacy; health literacy